KEMITRAAN SOSIAL EKONOMI MASYARAKAT DENGAN PERUSAHAAN UNTUK MENGISI QUO VADIS PENGENTASAN KEMISKINAN INDONESIA - Kris Kyantoro (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2012)
AbstractThe Partnership Model which have been created at the time of the practical activity was designed as an effort to develop local potential and resources in its form an access to the Corporate Social Responsibility (CSR) Program in handling the poverty problem. The local poverty called as artificial poverty that is referred to the poor condition which is caused by internal and external factors. This condition is characterized by lack of income and financial capital of the poor, but they are still having some valuable assets, or they are strong enough  to access certain resources for their own capacity building and welfare. The research result was shown that the early model may just include partnership in the social aspect, while the local economic empowerment aspect in the partnership have not optimally achieved.Its limitation was mainly due to the factor of the company program option which over concentrate on social charity activities in their CSR implementation. Limitations of the CSR Program implementation and also weaknesses and improvement needs of the model which led to the economic empowerment aspect and strengthening of the social aspect further are accommodated in the program design that aimed to strengthen the social economic in the three sectors relationships involving community, local government, and company. The model improvement implementation can be a seedbed media for the principles of the partnership. The Partnership Model of Socio-Economic of the Community with Company for Overcoming Poverty is a pattern of partnership which  able to increase the social awareness, an entrepreneurship spirits, and the community incomes. Keywords: artificial poverty, CSR, socio-economicpartnership, three sectors AbstrakModel Kemitraan yang dikembangkan pada saat kegiatan praktikum didesain sebagai upaya pengembangan potensi dan sumber lokal yang berupa akses pada Program Corporate Social Responsibility (CSR) dalam penanganan masalah kemiskinan. Kemiskinan lokal disebut artificial poverty yaitu kondisi miskin yang disebabkan oleh faktor internal dan eksternal. Kondisi ini ditandai dengan kekurangan penghasilan dan modal finansial kelompok miskin, namun mereka masih memiliki aset berharga tertentu atau masih dapat mengakses sumber daya tertentu bagi peningkatan kapasitas dan kesejahteraannya. Hasil penelitian menunjukkan bahwa Model Kemitraan (model awal) baru dapat mencakup aspek sosial sedangkan aspek pemberdayaan ekonomi lokal belum optimal tercapai. Keterbatasan tersebut terutama disebabkan oleh faktor pilihan program dari perusahaan yang bersubstansi pada kegiatan-kegiatan derma sosial pada pelaksanaan CSR-nya. Keterbatasan implementasi Program CSR beserta kelemahan  dan kebutuhan penyempurnaan model yang bermuara pada aspek pemberdayaan ekonomi dan penguatan aspek sosial selanjutnya diakomodir dalam desain penyempurnaan program yang diarahkan pada penguatan kemitraan sosial ekonomi masyarakat dalam  relasi tiga sektor yang melibatkan warga, pemerintah setempat, dan perusahaan. Implementasi penyempurnaan model  telah mampu menjadi media persemaian bagi prinsip-prinsip kemitraan. Model Kemitraan Sosial Ekonomi Masyarakat dengan Perusahaan untuk Mengatasi Kemiskinan (model akhir) merupakan pola kemitraan yang mampu meningkatkan kesadaran sosial, jiwa wirausaha, dan penghasilan masyarakat.Kata-kata kunci: artificial poverty, CSR, kemitraan sosial ekonomi, tiga sektor